Maguindanaon Love Songs as Tool and Springboard in Teaching Figurative Language for Maguindanaon Culture Preservation (Journal of Natural Language and Linguistics, 2023)
Filipinos have valued the use of songs as springboard in teaching figurative language as a vital tool to communicate thoughts feelings and emotions to convey messages. Halliday (1975). Figurative language is a used of words or expression in non-literal way to convey more vivid imaginatively. Thus, the use of literary texts and excerpts as teaching resources for English language teaching is beneficial for various reasons. English language teachers use literary texts in the classroom because of the vital role that literature plays in keeping students interested. The present study aims to identify the students’ level of competence in figurative language before and after teaching using Maguindanaon love songs English translations on Grade 7 students of Cotabato City National High School - Main Campus and to understand Maguindanaon culture of courtship and marriage by analyzing Maguindanaon love songs grounded on Ferdinand de Saussure’s Structuralism Theory. This study utilized the explanatory sequential mixed method design. Hence, the study revealed that, after a four-day exposure to Maguindanaon love songs as springboard to figurative lessons, the study found out that there is high significant difference between the means of the pre- and post-test scores with t28 = 12.53, p < 0.001 and an effective size of 2.33, which implied that the intervention material is highly effective for improving learners’ performance in their understanding of basic figurative languages. Furthermore, simile, metaphor, personification, hyperbole and alliteration are the five common figurative languages identified using a thematic analysis. The study concluded that, the use of English translations of Maguindanaon love songs are highly effective in boosting learners’ performance in English 7, notably their knowledge of basic figurative languages as indicated by the results made after the test. The paper suggested that, teachers can incorporate and preserve Maguindanaon literature love songs and use as example in the textbooks so that the appreciation of culture would still be present in the up coming generation. Thus this serves as reference for the future research endeavour.